16
$\begingroup$

$z^5+z^4+z^3+z^2+z+1 = 0$

I can't figure this out can someone offer any suggestions?

Factoring it into $(z+1)(z^4+z^2+1)$ didn't do anything but show -1 is one solution.

I solved for all roots of $z^4 = -4$ but the structure for this example was more simple.

$\endgroup$
  • 8
    $\begingroup$ Doesn't the polynomial look a lot like a partial sum of a familiar series? $\endgroup$ – Daniel Fischer Oct 18 '15 at 20:49
  • 4
    $\begingroup$ Whilst the given solutions are neater, you should also learn that the factoring you did gave a quadratic in $z^2$ that you know how to solve - so nothing more clever is actually required here. $\endgroup$ – Keith Oct 19 '15 at 0:09
45
$\begingroup$

Note that $(z-1)(1+z+z^2+z^3+z^4+z^5) = z^6-1$. Solve $z^6-1=0$ and discard the $z=1$ solution (which comes from the $z-1$ factor).

$\endgroup$
  • $\begingroup$ this is clearly the best way :) $\endgroup$ – Ant Oct 18 '15 at 20:57
  • 1
    $\begingroup$ Although I should have seen the solution the other ways, this will allow me to utilize the method I used previously. $\endgroup$ – Aspiring Mathematician Oct 18 '15 at 21:01
6
$\begingroup$

Hint:

Since $$z^4+z^2+1=(z^2+1)^2-z^2=(z^2+z+1)(z^2-z+1)$$ Solve $z^2+z+1=0$ and $z^2-z+1=0$ by using the quadratic formula: $$z^2+z+1=0\implies z_{1,2}=\frac{-1\pm\sqrt{1-4}}{2}=-\frac{1}{2}\pm\frac{\sqrt{3}}{2}i$$ $$z^2-z+1=0\implies z_{3,4}=\frac{1\pm\sqrt{1-4}}{2}=\frac{1}{2}\pm\frac{\sqrt{3}}{2}i$$

$\endgroup$
5
$\begingroup$

Here is another way to pursue this (just for fun!).

Recall that for $|x| < 1$ we have:

$$\frac{1}{1-x} = 1 + x + x^2 + x^3 + \cdots$$

Multiplying both sides by $x^6$ yields:

$$\frac{x^6}{1-x} = x^6 + x^7 + x^8 + x^9 + \cdots$$

Now we subtract the former line from the latter:

$$\frac{x^6 - 1}{1-x} = -(1 + x + x^2 + x^3 + x^4 + x^5)$$

We now multiply both sides by $-1$ to obtain your original expression:

$$\frac{x^6 - 1}{x-1} = 1 + x + x^2 + x^3 + x^4 + x^5$$

In one way, this is no different than the suggestion in your accepted answer. But I think (hope) seeing the connection arise in a different manner is of interest. Anyway, at this point you seek to find the roots of $x^6 - 1 = (x^3 + 1)(x^3 - 1)$, and you can now factor the latter two parenthetical expressions as the sum and difference of cubes, respectively, to find the roots.

(Noting that/why $x\neq 1$.)

$\endgroup$
2
$\begingroup$

Factoring it into $(z+1)(z^4+z^2+1)$ didn't do anything but show -1 is one solution.

False.

It also shows the remaining four solutions are roots of $z^4 + z^2 + 1 = 0$.

$\endgroup$
  • 2
    $\begingroup$ Which is a quadratic equation in $x=z^2$. In fact, it's one of my favorite equations. $\endgroup$ – Joel Oct 19 '15 at 10:15
1
$\begingroup$

$$z^5+z^4+z^3+z^2+z+1 = 0 \Longleftrightarrow$$ $$(z+1)(z^2-z+1)(z^2+z+1) = 0 \Longleftrightarrow$$ $$z+1=0 \vee z^2-z+1=0 \vee z^2+z+1=0 \Longleftrightarrow$$ $$z=-1 \vee z=\frac{1\pm\sqrt{-3}}{2} \vee z=\frac{-1\pm\sqrt{-3}}{2} \Longleftrightarrow$$ $$z=-1 \vee z=\frac{1\pm i\sqrt{3}}{2} \vee z=\frac{-1\pm i\sqrt{3}}{2} $$

$\endgroup$
1
$\begingroup$

$$\begin{align}z^6&=1\\ z^6-1&=0\\ (z-1)(\underbrace{z^5+z^4+z^3+z^2+z+1}_{f(z)})&=0 \end{align}$$ Hence the solutions to $f(z)$ are $$\begin{align}z^6&=1=e^{i2\pi} &&(z\neq1)\\ z&=e^{i\frac {2n\pi}6}=e^{i\frac {n\pi}3}&& (n=1,2,3,4,5)\quad\blacksquare\end{align}$$

$\endgroup$
0
$\begingroup$

I quote: Factoring it into (z+1)(z4+z2+1)(z+1)(z4+z2+1) didn't do anything but show -1 is one solution. Put $z^2=u$ then you will find the solutions.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.